Paraneoplastic neurological autoimmunity and survival in small-cell lung cancer. - Maddison, P; Lang, B (2008)
The autoimmune disorder of Lambert-Eaton myasthenic syndrome (LEMS) associates with small cell lung carcinoma (SCLC) in 50-60% of cases. It has been postulated that patients who harbour paraneoplastic neurological syndromes such as LEMS have an improved tumour prognosis compared to other patients with the tumour but without neurological deficit. In this intermediate report of an ongoing prospective study, 100 consecutive patients with biopsy-proven SCLC underwent full neurological examination and serum was taken for autoantibody analysis. Antibodies to voltage-gated calcium channels were detected in 10 patients, however only 4 had clinical and electrophysiological features of LEMS, 1 had limbic encephalitis, whilst the remaining 5 had no neurological signs. A further 6 patients had onconeural antibodies; only one had a paraneoplastic syndrome, sensory neuropathy. The median survival of the four antibody positive LEMS patients (19.6 months) was considerably greater than that for the antibody negative (8.9 months) or antibody positive patients as a whole (10.5 months). Although preliminary, these results suggest that functionally effective antibodies present in the sera of patients with LEMS may confer a survival advantage.